Evolution of Telehealth-Its Impact on Palliative Care and Medication Management - Syed N. Imam; Ursula K. Braun; Mary A. Garcia; Leanne K. Jackson (MDPI AG, 2024)
Palliative care plays a crucial role in enhancing the quality of life for individuals facing serious illnesses, aiming to alleviate suffering and provide holistic support. With the advent of telehealth, there is a growing interest in leveraging technology to extend the reach and effectiveness of palliative care services. This article provides a comprehensive review of the evolution of telehealth, the current state of telemedicine in palliative care, and the role of telepharmacy and medication management. Herein we highlight the potential benefits, challenges, and future directions of palliative telemedicine. As the field continues to advance, the article proposes key considerations for future research, policy development, and clinical implementation, aiming to maximize the advantages of telehealth in assisting individuals and their families throughout the palliative care journey. The comprehensive analysis presented herein contributes to a deeper understanding of the role of telehealth in palliative care and serves as a guide for shaping its future trajectory.